An Association Rule Model of Course Recommendation in MOOCs: Based on edX Platform - Tan, Min; Wu, Maoguo (European Scientific Journal, ESJ, 2018)
The rapid development of the Internet has promoted online education as a new method of education. This paper analyzes the edX platform from various aspects, such as business environment and industry development, technology maturity, and recommendation algorithms and their feasibility. This paper mainly focuses on the curriculum recommendation mechanism under association rules on the edX platform. With the fast development of online education platform, curriculum recommendation technology has matured to a high extent. The recommendation mechanism based on association rules chosen by edX also proves to be feasible at data acquisition level and technical level. However, some defects of this mechanism per se have brought certain risks and limitations to edX’s future sustainable development.